Exploration of Potent Human α-Glucosidase Inhibitors Using In Silico Approaches: Molecular Docking, DFT, Molecular Dynamics Simulations, and MMPBSA - Jyoti Bashyal; Bimal Kumar Raut; Siddha Raj Upadhyaya; Kabita Sharma; Niranjan Parajuli (Journal of Chemistry)
Inhibiting α-glucosidase, a key enzyme in carbohydrate hydrolysis, can potentially control diabetes mellitus. Although commercially available drugs effectively lower blood glucose levels to mitigate hyperglycemia, their associated gastrointestinal side effects necessitate the exploration of explicit inhibitors with minimal side effects. We studied a library of 80 secondary metabolites ascribed to their antidiabetic properties and screened the most potent inhibitors using a comprehensive in silico approach, including molecular docking, DFT study, MD simulation, PCA, MMPBSA calculation, and pharmacokinetic analysis. Scolopianate A and ponasterone A emerged as potent α-glucosidase inhibitors, forming hydrogen bonds with the catalytic diad and exhibiting prominent binding affinities of −8 kcal/mol. Further analyses encompassed significant reactivity at the catalytic site and stable protein-ligand complexes, as asserted by 100 ns RMSD, RMSF, Rg, SASA, H-bond, and PCA-based free energy landscape analysis. The subsequent analysis of MMPBSA indicating a higher binding free energy of these compounds compared to reference ligand, acarbose further strengthened the validity of these findings. Furthermore, drug-like behavior and favorable ADMET profiles affirmed scolopianate A and ponasterone A as robust α-glucosidase inhibitors. These findings highlight their promise for future drug development targeting α-glucosidase inhibition in diabetes management; however, more research needs to be conducted.